Ion-specific effects on the kinetics of mineral dissolution - Ruiz-Agudo, E.; Urosevic, M.; Putnis, Christine; Rodríguez-Navarro, C.; Cardell, C.; Putnis, Andrew (2011)
Specific effects of background electrolytes on mineral growth and dissolution can be interpreted on the basis of the ability of ions to modify solute hydration, in a similar way to the systematic effects of inorganic ions on precipitation, structure and function of organic macromolecules (i.e., the Hofmeister effect). Here, the effect of a range of background electrolytes (sodium and chloride salts) on dolomite (Ca0.5Mg0.5CO3) reactivity was investigated as a model system by measuring dissolution rates using in-situ Atomic Force Microscopy. The systematic trends found for the different ions are interpreted in terms of characteristic parameters of background ions such as effective hydrated radii. Entropic effects associated with the ordering of solvent molecules induced by constituting cations from the crystal ultimately dictate how electrolytes affect dissolution rates. In dilute electrolyte solutions, ion-ion interactions dominate and the stabilisation of the solvation shell of ions constituting the crystal, by counter-ions present in solution enhances the unfavourable entropic effect on dolomite dissolution. The tendency for electrolytes to form ion pairs in solution reduces such an effect, thus leading to an inverse correlation between dissolution rates and background ion separation in solution. On the other hand, in concentrated saline solutions the interaction between background ions and water molecules determines the hydration of a constituent ion immersed in an electrolyte solution. In this case, dissolution rates correlate with the mobility of background ions and, therefore, with their effective hydration radii. The observed effects of background ions on growth and dissolution could be applicable for other inorganic systems where the Hofmeister effect has been reported. © 2011 Elsevier B.V.